العجائبية في القصة القصيرة الجزائرية - ضامن, عويشة (كلية الأدب العربي والفنون, 2025)
" العجائبية في القصة القصيرة الجزائرية، دراسة في قصص جنِّية البحر لجميلة زنِّير أنموذجا" يُّعد توظيف العجائبي في الأدب من أبرز الأساليب الفنية التي تلجأ إليها الكتابة السردية الحديثة، لما يتيحه من إمكانيات للتعبير عن الواقع بأساليب غير تقليدية، تتجاوز المباشر والمألوف. وفي السياق الجزائري، برز هذا التوظيف بشكل لافت في القصة القصيرة، مما يجعل دراسته أمرًا جديرًا بالاهتمام، ومن هنا قمنا بمعالجة هذا الموضوع الموسوم:" العجائبية في القصة القصيرة الجزائرية، دراسة في قصص جنِّية البحر لجميلة زنَّير أنموذجا" تتناول هذه المذكرة إشكالية كيفية تجلي البعد العجائبي في القصة القصيرة الجزائرية، لاسيما في مجموعة "جنّية البحر" لجميلة زنير. وتنطلق الدراسة من فرضية مفادها أن العجائبي يُستخدم كأداة فنية لتجاوز الواقع المألوف، وللتعبير عن دلالات رمزية ترتبط بالواقع الاجتماعي. وقد تم اعتماد المنهج الوصفي التحليلي في تناول النصوص، حيث كشفت النتائج أن العجائبي في هذه القصص لا يقتصر على خلق أجواء غرائبية، بل يساهم في تعميق البنية الدلالية للنصوص ويمنحها بعدًا تأويليًا ثريًا، وخلاصة القول، إن تجربة جميلة زنير في توظيف العجائبي تمثل نموذجًا متميزًا في القصة القصيرة الجزائرية الحديثة، حيث استطاعت أن تمزج بين الجمالية الفنية والعمق الرمزي، ما يجعل أعمالها جديرة بالدراسة والاهتمام النقدي. The Marvelous in the Algerian Short Story, a Study of the Sea Fairy Tales of Djamila Zenir as a Model The use of the fantastic in literature is one of the most prominent artistic methods employed by modern narrative writing, as it offers possibilities for expressing reality in unconventional ways that transcend the direct and familiar. In the Algerian context, this use has been prominent in the short story, making its study worthy of attention. Hence, we have addressed this topic entitled: "The Marvelous in the Algerian Short Story: A Study of Djamila Zenir's "The Fairy of the Sea" Stories as a Model." This paper addresses the problematic aspect of the fantastic in the Algerian short story, particularly in Djamila Zenir's collection "The Fairy of the Sea." The study is based on the hypothesis that the fantastic is used as an artistic tool to transcend familiar reality and express symbolic connotations related to social reality. The descriptive-analytical approach was adopted in dealing with the texts, as the results revealed that the fantastic in these stories is not limited to creating a strange atmosphere, but rather contributes to deepening the semantic structure of the texts and gives them a rich interpretive dimension. In conclusion, Djamila Zenir's experience in employing the fantastic represents a distinguished model in the modern Algerian short story, as she was able to combine artistic aesthetics with symbolic depth, which makes her works worthy of study and critical attention.
دراسة في قصص جنية البحر لجميلة زنير أنموذجا
Keywords: العجائبي، القصة القصيرة، جنِّية البحر، جميلة زنِّير; the fantastic, short story, mermaid, Djamila Zenir